Value of contrast-enhanced ultrasonography in radiofrequency ablation of secondary hyperparathyroidism. Issue 1 (1st January 2021) - Qin, Xiachuan; Wang, Baofu; Li, Boliang; Lin, Changwei; Liu, Xuebin; Xie, Xisheng
Abstract: Objectives: The purpose of the current study was to determine the performance of contrast-enhanced ultrasound (CEUS) in the assessment of radiofrequency ablation (RFA) of hyperplastic parathyroid glands due to secondary hyperparathyroidism (SHPT). Methods: Thirty-two patients, each with ≥4 hyperplastic parathyroid glands due to SHPT, underwent RFA via hydro-dissection. CEUS was performed in each patient before and during RFA. The patients in whom the intact parathyroid hormone (iPTH) level did not decrease to 300 pg/ml were examined by CEUS. The iPTH, serum calcium, and serum phosphorus levels before and after RFA were compared. Results: Ablation was achieved in all patients (131 ablated glands). The volume of the glands was 479.88 ± 549.3mm 3 . The pre-operative and day 1 post-operative iPTH levels were 2355 ± 1062 and 292.7 ± 306.8 pg/ml, respectively. Three nodules in three patients showed little enhancement on CEUS on post-operative day 1. The iPTH level was <300 pg/mL on post-operative day 1 in 23 patients, which indicated complete ablation; follow-up evaluations were therefore performed. The pre- and post-operative iPTH levels in the 23 patients were 2113 ± 787.2 and 106.2 ± 84.62 pg/ml, respectively ( p  < 0.05), and the 6- and 12-month post-operative iPTH levels were 111.1 ± 56.57 and 117.6 ± 97.08 pg/ml, respectively ( p  > 0.05). Conclusions: CEUS-guided RFA is effective and feasible for the treatment of ≥4 hyperplastic parathyroid glands. CEUS was shown to assist the surgeon before, during, and after RFA. CEUS on post-operative day 2, but not immediately post-operatively, was shown to accurately reflect gland perfusion.